Effects of police ethics training on ethnic prejudice and social dominance orientation. (June 2023) - van Droogenbroeck, Filip; Spruyt, Bram; Ivković, Sanja Kutnjak
Police administrators are looking for concrete pathways to fight the phenomenon of (ethnic) prejudice among members of the police force. Surprisingly, few studies have assessed the effectiveness of existing police ethics training programs on prejudice and social dominance orientation. Therefore, we assessed the impact of a 1-day training called the Holocaust, Police, and Human Rights (HPH) program on the attitudes related to ethnic prejudice and social dominance orientation of 223 members of the Belgian police. Analyses of three-wave panel data indicate that HPH training reduced ethnic prejudice and social dominance orientation. For ethnic prejudice, the reduced effects were maintained after 1 month in the follow-up study. However, the effect of training on prejudice was weaker for police officers who were more often exposed to victims and perpetrators of crime. No lasting effect of HPH training was found for social dominance orientation.